Measuring objective fatigability and autonomic dysfunction in clinical populations: How and why? - Millet, Guillaume Y.; Bertrand, Mathilde F.; Lapole, Thomas; Féasson, Léonard; Rozand, Vianney; Hupin, David (Frontiers in Sports and Active Living, 2023)
Fatigue is a major symptom in many diseases, often among the most common and severe ones and may last for an extremely long period. Chronic fatigue impacts quality of life, reduces the capacity to perform activities of daily living, and has socioeconomical consequences such as impairing return to work. Despite the high prevalence and deleterious consequences of fatigue, little is known about its etiology. Numerous causes have been proposed to explain chronic fatigue. They encompass psychosocial and behavioral aspects (e.g., sleep disorders) and biological (e.g., inflammation), hematological (e.g., anemia) as well as physiological origins. Among the potential causes of chronic fatigue is the role of altered acute fatigue resistance, i.e. an increased fatigability for a given exercise, that is related to physical deconditioning. For instance, we and others have recently evidenced that relationships between chronic fatigue and increased objective fatigability, defined as an abnormal deterioration of functional capacity (maximal force or power), provided objective fatigability is appropriately measured. Indeed, in most studies in the field of chronic diseases, objective fatigability is measured during single-joint, isometric exercises. While those studies are valuable from a fundamental science point of view, they do not allow to test the patients in ecological situations when the purpose is to search for a link with chronic fatigue. As a complementary measure to the evaluation of neuromuscular function (i.e., fatigability), studying the dysfunction of the autonomic nervous system (ANS) is also of great interest in the context of fatigue. The challenge of evaluating objective fatigability and ANS dysfunction appropriately (i.e.,. how?) will be discussed in the first part of the present article. New tools recently developed to measure objective fatigability and muscle function will be presented. In the second part of the paper, we will discuss the interest of measuring objective fatigability and ANS (i.e. why?). Despite the beneficial effects of physical activity in attenuating chronic fatigue have been demonstrated, a better evaluation of fatigue etiology will allow to personalize the training intervention. We believe this is key in order to account for the complex, multifactorial nature of chronic fatigue.